Genome-Wide Characterization and Functional Analysis of CsDOF Transcription Factors in Camellia sinensis cv. Tieguanyin Under Combined Heat–Drought Stress - Yingxin Wen; Cunyi Tan; Yujie Zhang; Hua Wu; Dian Chen; Heng Yue; Zekai Ding; Shijiang Cao; Kehui Zheng (Plants, 2025)
Tieguanyin tea, celebrated as one of China’s top ten famous teas, is highly regarded for its unique flavor and taste. However, recent intensification of global warming has escalated the occurrence of abiotic stresses, posing significant threats to the growth, development, yield, and quality of Tieguanyin tea plants. DOF (DNA-binding one zinc finger protein), a plant-specific transcription factor, plays a critical role in plant development and stress response. In this study, we identified and analyzed 58 CsDOF genes across the whole genome, which were found to be randomly and unevenly distributed across 15 chromosomes. A phylogenetic tree was constructed using DOF genes from Arabidopsis thaliana and Tieguanyin, categorizing these genes into 10 subgroups. Collinearity analysis revealed homologous gene pairs between CsDOF and OsDOF(19 pairs), StDOF (101 pairs), and ZmDOF (24 pairs). Cis-acting element analysis indicated that CsDOF genes contain elements related to both stress and hormone responses. Heat map analysis demonstrated that subfamily C2 predominantly regulates the growth and development of roots, stems, and leaves in Tieguanyin. Tertiary structure analysis of CsDOF proteins revealed diverse structures, underscoring the functional variability within the CsDOF gene family. Furthermore, qRT-PCR analysis was employed to assess the expression profiles of 13 CsDOF genes under high-temperature and drought conditions. Notably, CsDOF51 and CsDOF12 exhibited significant expression changes under drought and high-temperature stress, respectively, while CsDOF44 showed significant changes under both conditions. This study provides foundational knowledge of the CsDOF gene family and offers novel insights for enhancing the drought and heat tolerance of Tieguanyin tea.